Avaliação numérico-experimental da hidrodinâmica e da transferência de oxigênio em biorreator coluna de bolhas utilizando fluidodinâmica computacional - Silva, Ana Carolina Borges (2023)
Pneumatic bioreactors are increasingly employed in bioprocesses due to their effective heat and mass transfer, rapid mixing, and efficient suspension of solids. Computational Fluid Dynamics (CFD) has emerged as a key tool for studying transport phenomena in engineering equipment, utilizing conservation equations for momentum, energy, and mass to describe fluid dynamics. This study evaluates the hydrodynamics of a square-section bubble column bioreactor both experimentally and numerically through CFD simulations. Key parameters such as global gas holdup (αG), volumetric oxygen transfer coefficient (kLa), and mean (γAV) and maximum (γmax) shear rates are analyzed. Numerical simulations employ the Euler-Euler approach and vary bubble diameters (4, 5, and 6 mm) alongside specific air feed rates (1.0, 3.0, and 5.0 vvm), incorporating drag and lift interfacial forces. Following the selection of the optimal mathematical model, population balance equations (PBE) are integrated into the fluid dynamic model to predict bubble size distribution and assess the impact of breakage (Luo model) and coalescence (turbulent model) phenomena on air distribution and hydrodynamic parameters. These are compared with initial simulation results to refine the model. Simulated values of αG, kLa, γAV, and γmax is compared with experimental and literature data to validate the mathematical model and numerical approach. Results indicate that simulations incorporating lift forces closely match experimental outcomes, with the smallest bubble diameter (4 mm) yielding the highest parameter values. Notably, maximum shear rate (γmax) predictions show good agreement with semi-empirical correlations when considering interactions of breakage and coalescence. Adjusting the fluid dynamic model with PBE confirms accurate prediction of bubble size distribution and Sauter mean diameters within experimental ranges. The coupled CFD-PBM model, considering breakage and coalescence effects, provides superior predictions for gas retention and volumetric oxygen transfer coefficient compared to experimental values. For mean shear rate, the model aligns well with semi-empirical correlations, while maximum shear rate predictions maintain consistent order of magnitude when considering interaction effects.